JOHN GRISHAM AND HIS NOVEL "A TIME TO KILL": LITERARY ELEMENTS, LANGUAGE AND CHARACTERS (American Journal of Interdisciplinary Research and Development, 2023)
John Grisham, a master of legal thrillers, rose to literary prominence with his gripping novel "A Time to Kill." Published in 1989, this novel showcase Grisham's prowess in weaving intricate narratives within the legal framework. In this linguistic analysis, we delve into the literary elements, language choices, and characters that contribute to the novel's compelling storytelling.